Research Development in University Nursing Departments in South Africa: description of a research development model - Uys, LR; Klopper, HC (South African Journal of Higher Education, 2016)
In the field of research, nursing is in a catch-up mode and the need to rapidly develop the capacity to do research that addresses the health needs of the population is being addressed by university nursing schools in South Africa. The design and implementation of the research development programme intended to surmount this problem is described in this paper. The programme aimed at developing lead researchers within each nursing department to lead a research programme on a selected health topic. The focus was on the person as well as the department as the research platform. The lead researchers were assisted in developing a research team for their programme, in becoming part of an international network, working with a research mentor, in submitting proposals for external funding and preparing for NRF rating. This was done through a series of workshops and the appointment of a mentor for each lead researcher. The programme was successful in getting lead researchers to establish research teams in their own institutions, work with mentors and apply for external research funding.